Anti-oil-dirt photovoltaic panel self-cleaning coating and preparation method thereof

By using hollow nanotitanium dioxide and sodium perfluorooctane sulfonate coatings on photovoltaic panels, combined with microbial-based oil degrading agents, the super hydrophilic/oleophobic coating is formed, which solves the problem of difficult removal of oil pollution and achieves efficient Oil degradation and panel cleaning reduce cleaning costs and maintain the efficient power generation performance of the panel.

CN119264715AActive Publication Date: 2025-01-07GUANGZHOU XINYI NEW MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411540374.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

It is difficult to completely remove oil pollution on photovoltaic panels, resulting in reduced light absorption efficiency and material corrosion. Traditional cleaning methods may cause secondary damage to the panels and have strong adhesion and stability, making it difficult for the existing technology to effectively prevent and control.

Method used

Using anti-oil scale photovoltaic panel self-cleaning coatings including hollow nanotitanium dioxide and sodium perfluorooctane sulfonate, a super hydrophilic/oleophobic coating is formed through nanotechnology and microbial-based oil-fouling degrading agents, using photocatalysis and biodegradation synergistic effects , realize the degradation and removal of oil pollution.

Benefits of technology

It significantly improves the cleaning effect of photovoltaic panels, reduces cleaning costs, demonstrates excellent stability and anti-oil stain performance, can effectively degrade oil stains in high humidity and dry environments, and maintains the cleanliness and high power generation efficiency of the panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264715A_ABST
    Figure CN119264715A_ABST
Patent Text Reader

Abstract

The invention discloses an oil-stain-resistant photovoltaic panel self-cleaning coating and a preparation method thereof, the oil-stain-resistant photovoltaic panel self-cleaning coating comprises the following components in parts by weight: 17-20 parts of hollow nano titanium dioxide and 5-7 parts of sodium perfluorooctane sulfonate, and the hollow nano titanium dioxide is prepared by coating the outer surface of silicon dioxide with the hollow nano titanium dioxide and then coating the hollow nano titanium dioxide with the sodium perfluorooctane sulfonate. And removing hollow anatase nano titanium dioxide formed by the silicon dioxide core, wherein the hollow nano titanium dioxide contains an oil stain degradation agent. The coating disclosed by the invention has double effects of hydrophilicity, oleophobicity and oil stain degradation, the cleaning effect is greatly improved, the cleaning cost is reduced, and excellent stability is also shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to an anti-grease and dirt self-cleaning coating for photovoltaic panels and a preparation method thereof. Background Art

[0002] Photovoltaic power generation, as a new type of clean energy, has many advantages over traditional power generation, such as environmental protection, pollution-free, and noise-free. It is a sustainable new energy that my country has vigorously developed in recent years. Taking January-April 2024 as an example, the cumulative installed capacity of photovoltaic power generation in China has reached an astonishing 671.47 million kilowatts, a year-on-year surge of 52.4%. However, with the rapid development of the photovoltaic industry, the dust and oil pollution problems on photovoltaic panels have gradually become prominent, which has had an unignorable impact on the performance of photovoltaic systems. Although my country has made significant progress in the prevention and control of dust pollution on photovoltaic panels, the negative impact of dust on photovoltaic panels has been effectively reduced through the application of innovative technologies such as self-cleaning coatings, self-cleaning robots, and spray devices, but the prevention and control of oil pollution still faces many technical challenges. Oil attached to photovoltaic panels not only significantly reduces the light absorption efficiency and leads to a sharp drop in power generation, but also the complex chemical composition in the oil may corrode the photovoltaic panel materials, thereby shortening their service life. What is more serious is that the oil has extremely strong adhesion and stability, making it difficult to completely remove it by traditional cleaning methods. Even if high-pressure water guns or chemical cleaning agents are used for cleaning, it may not be possible to completely remove the oil stains, leaving hidden dangers, and may even cause secondary damage to the photovoltaic panels. Therefore, the prevention and control of oil pollution has become a key issue that needs to be urgently addressed in the development of the current photovoltaic industry. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a self-cleaning coating for photovoltaic panels that is resistant to oil and dirt. The coating of the present invention has the dual effects of being hydrophilic and oleophobic and degrading oil stains, which greatly improves the cleaning effect, reduces the cleaning cost, and also exhibits excellent stability.

[0004] The technical solution adopted by the present invention is:

[0005] A self-cleaning coating for photovoltaic panels that resists oil and dirt, characterized in that it comprises the following components: it comprises the following components in parts by weight: 17-20 parts of hollow nano-titanium dioxide and 5-7 parts of sodium perfluorooctane sulfonate, wherein the hollow nano-titanium dioxide is a hollow anatase nano-titanium dioxide formed by coating the outer surface of silicon dioxide and then removing the silicon dioxide inner core, and the hollow nano-titanium dioxide contains an oil degradation agent.

[0006] Sodium perfluorooctane sulfonate mainly provides non-polar fluorine elements and polar hydrophilic segments on the surface of the coating. The introduction of fluorine elements will reduce the surface free energy of the coating to a certain extent and improve the hydrophobic and oleophobic properties. The strong complexation between fluoride ions and titanium dioxide can increase the high electronegativity of titanium dioxide, improve the charge separation efficiency, significantly promote the hole transfer on the surface of titanium dioxide and increase the activity of hydroxyl radicals, thereby increasing its photocatalytic degradation efficiency for organic pollutants. Sodium perfluorooctane sulfonate cannot be too much. If too much is added, the increase in fluorine elements will cause steric hindrance between water and the hydrophilic segments on the surface of titanium dioxide, resulting in a decrease in its hydrophilic properties, which hinders the release of hydroxyl radicals and oil degradation agents through the hydration film to the surface to remove organic pollutants during the photocatalytic process, and weakens the anti-oil performance.

[0007] Preferably, the particle size of the nano titanium dioxide is 55-80 nm.

[0008] Preferably, the oil degradation agent is a microbial-based oil degradation agent.

[0009] A method for preparing an anti-oil-fouling photovoltaic panel self-cleaning coating is characterized in that it comprises the following steps: dispersing 17-20 parts of hollow nano-titanium dioxide containing an oil-fouling degradation agent in an appropriate amount of volatile organic solvent, and then adding 5-7 parts of sodium perfluorooctane sulfonate dropwise to obtain an anti-oil-fouling coating.

[0010] Preferably, the hollow nano titanium dioxide is a hollow anatase nano titanium dioxide formed by coating the outer surface of silicon dioxide and then removing the silicon dioxide core, and the preparation method comprises the following steps:

[0011] A1. Mix 25-34 parts of nano-silicon dioxide with an appropriate amount of ethanol, grind until there are no large-particle agglomerates visible to the naked eye, and then disperse them in an appropriate amount of water, add 3-9 parts of nitric acid, add 15-25 parts of tetrabutyl titanate, and then adjust the pH of the system to neutral, react for a period of time, and prepare a titanium dioxide sol-gel; the particle size of the nano-silicon dioxide is 55-80nm;

[0012] A2. The titanium dioxide sol-gel is centrifuged, washed with ethanol to remove impurities, and then the ethanol is evaporated to remove the ethanol. The obtained nano powder is heated to temperature T in a strong alkaline solution to be etched to remove nano silicon dioxide, and then calcined at high temperature to obtain hollow nano titanium dioxide.

[0013] The nano-silica template has a small particle size, which will further reduce the particle size and internal hollow volume of the hollow nano-titanium dioxide prepared subsequently, ultimately resulting in a reduction in the roughness of the coating surface, a reduction in the amount of oil degradation agent that can be loaded, and a reduction in the coating's anti-oil performance. If the nano-silica template has an excessively large particle size, it will increase the particle size and internal hollow volume of the hollow nano-titanium dioxide prepared subsequently, ultimately resulting in an increase in the roughness of the coating surface.

[0014] Nitric acid mainly affects the hydrolysis rate of tetrabutyl titanate and the crystal form of titanium dioxide generated. The addition of nitric acid can slow down the hydrolysis rate of tetrabutyl titanate, otherwise it will cause the hydrolysis to be too fast, forming an overly thick titanium dioxide layer on the surface of the silica template, making the final titanium dioxide particles too large in size, increasing the roughness of the coating surface, and reducing the transmittance in the visible light region, affecting the photovoltaic power generation efficiency. However, too much nitric acid will cause the titanium dioxide crystal form generated by the hydrolysis of tetrabutyl titanate to be converted from anatase to rutile, and rutile titanium dioxide is photocatalytically inert and has no ability to degrade organic matter, resulting in a decrease in the photocatalytic activity of the final prepared coating and a decrease in the degradation rate of organic pollutants.

[0015] Preferably, the hollow nano titanium dioxide containing the oil degradation agent is prepared by the following steps:

[0016] B1. Place hollow nano-titanium dioxide in a container, control the air pressure in the container to be lower than the atmospheric pressure, and inject an oil degradation agent into the container so that the oil degradation agent completely covers the nano-titanium dioxide particles;

[0017] B2. Slowly release the system to normal air pressure to obtain hollow nano-titanium dioxide containing oil degradation agent.

[0018] If too much oil degradation agent is added and fails to completely enter the interior of the nano-titanium dioxide particles, the excess oil degradation agent can be washed away with ethanol.

[0019] Preferably, the nano silicon dioxide is prepared by the following steps:

[0020] C1. Mix 10-30 parts of water, 35-45 parts of industrial ammonia water, and 750-800 parts of ethanol, slowly add 38-40 parts of tetraethyl silicate, and react at a temperature of 40-55°C for a period of time to prepare SiO2 sol-gel; the industrial ammonia water is an aqueous solution containing 25% to 28% ammonia.

[0021] C2. After centrifuging the SiO2 sol-gel, the separated solid product is washed with ethanol, and then the ethanol is evaporated to remove the ethanol to obtain nano-silicon dioxide. The ethanol washing removes water, ammonia and unreacted tetraethyl silicate.

[0022] Preferably, the volatile organic solvent is ethanol.

[0023] Preferably, the temperature T is 82-88°C.

[0024] Preferably, the calcination temperature in step A2 is 450°C.

[0025] The coating formed by the anti-oil and dirt coating provided by the present invention has an excellent super hydrophilic / oleophobic effect. In high-humidity climate areas, it can form a water film on the surface of the photovoltaic panel through hydration, reduce the adhesion of oil stains, and keep the surface of the photovoltaic panel clean; the anti-oil and dirt photovoltaic panel self-cleaning coating has an excellent effect of decomposing oil stains. The hollow nano TiO2 (anatase crystal form) particles with photocatalytic activity cooperate with the bio-based oil stain degradation agent, which can desorb the oil stains on the surface and degrade them into carbon dioxide, water and other inorganic small molecules in a dry and water-free film environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the anti-grease and dirt photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention.

[0027] Figure 2 A comparison curve of transmittance in the visible light region between the photovoltaic panel glass coated with the anti-grease and anti-fouling photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention and the untreated photovoltaic panel glass.

[0028] Figure 3 This is an image of the degradation performance of organic pollutants on the glass surface coated with the anti-greasy photovoltaic panel self-cleaning coating characterized by fluorescence microscopy.

[0029] Figure 4 Degradation rate curve of the anti-greasy-fouling photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention in the anti-greasy-fouling performance test.

[0030] Figure 5 Degradation cycle curve of the anti-greasy-fouling photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention in the anti-greasy-fouling performance test.

[0031] Figure 6 Comparison curve of power generation efficiency of a photovoltaic panel coated with the anti-grease and anti-fouling photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention and an untreated photovoltaic panel before and after being placed in an outdoor environment for a long time. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is described in detail below in conjunction with specific implementation examples, but the present invention is not limited to the given examples.

[0033] Example 1

[0034] The specific preparation method of the anti-grease and dirt coating for photovoltaic panels provided by the present invention is as follows:

[0035] (1) 20 g of deionized water and 40 g of ammonia water were added to 780 g of anhydrous ethanol, and after stirring at room temperature for 30 minutes, 39 g of tetraethyl silicate was added dropwise, and then the temperature was maintained at 40° C. and the reaction was continued for 6 hours to prepare a SiO2 sol-gel. The above sol-gel was centrifuged, and the separated solid product was washed 3 times with anhydrous ethanol, and then dried at 80° C. to obtain 30 g of nano-SiO2 particles, which were used as a SiO2 template agent for later use;

[0036] (2) Put the SiO2 template and an appropriate amount of anhydrous ethanol into an agate mortar and grind them for 30 minutes. During the wet grinding process, an appropriate amount of anhydrous ethanol can be added to keep its volume as unchanged as possible. After the wet grinding is completed, the SiO2 template (containing anhydrous ethanol) is dispersed in 1000g of deionized water, and then 6.3g of nitric acid is added. After being fully stirred and mixed at room temperature, 20g of tetrabutyl titanate is added, and then ammonia water is added dropwise to adjust the pH of the system to neutral. The reaction is continued for 3 hours to prepare a nanoscale core-shell particle sol gel having a TiO2 (anatase crystal form) shell and a SiO2 core. After the above sol gel is centrifuged, the separated solid product is washed 3 times with anhydrous ethanol and dried at 80°C. The obtained nano powder is etched in a 1M sodium hydroxide solution at 85°C for 6 hours to remove the SiO2 template, and then calcined in a muffle furnace at 450°C for 2 hours to finally obtain 16g of hollow nano TiO2 (anatase crystal form) particles with a particle size of about 80 nanometers;

[0037] (3) Place the nano hollow TiO2 (rutile crystal form) particles in a sealed container, pump the internal pressure of the container to about 5 mbar through a vacuum pump, and then inject a bio-based oil degradation agent (SUKAZME-GRL3X of Weifang Yihao Biotechnology Co., Ltd. or SUKAClean GR / C of Sukehan (Weifang) Bioengineering Co., Ltd.) into the container using a syringe. After the bio-based oil degradation agent completely covers the hollow nano TiO2 (rutile crystal form) particles, slowly release the system to normal pressure. Due to the pressure difference, the bio-based oil degradation agent will be absorbed into the shell of the hollow nano TiO2 (rutile crystal form) particles, and after being rinsed three times with anhydrous ethanol, hollow nano TiO2 (rutile crystal form) particles containing the bio-based oil degradation agent are obtained;

[0038] (4) hollow nano-TiO2 (anatase crystal form) particles containing a bio-based oil degradation agent are dispersed in anhydrous ethanol, and then 6 g of sodium perfluorooctane sulfonate is added dropwise. After the reaction is continued for 2 hours at room temperature, an anti-oil self-cleaning coating for photovoltaic panels is prepared;

[0039] After the glass substrate used for the photovoltaic panel was rinsed twice with anhydrous ethanol and deionized water alternately, the coating was sprayed onto the surface of the photovoltaic glass panel, and the glass panel was kept horizontal during the spraying process. After curing at 50°C for 1 hour, an anti-oil and dirt photovoltaic panel self-cleaning coating was prepared on the surface of the photovoltaic glass panel.

[0040] Example 2

[0041] The difference between this embodiment and the embodiment is that the addition amount of each component is: 15g of tetrabutyl titanate, 30g of tetraethyl silicate, 10g of deionized water in step (1), 25g of nano-silicon dioxide obtained in step (1), 12g of nano-titanium dioxide obtained in step (2), and the etching temperature in step (2) is 82°C. The rest is the same as in embodiment 1.

[0042] Example 3

[0043] The difference between this embodiment and the embodiment is that the addition amount of each component is: 25g of tetrabutyl titanate, 40g of tetraethyl silicate, 30g of deionized water in step (1), 34g of nano-silicon dioxide obtained in step (1), 20g of nano-titanium dioxide obtained in step (2), and the etching temperature in step (2) is 88°C. Others are the same as in embodiment 1.

[0044] Example 4

[0045] The difference between this embodiment and the embodiment is that the addition amount of each component is: 35 g of ammonia water in step (1), 750 g of anhydrous ethanol in step (1), and 3 g of nitric acid in step (2), and the rest is the same as embodiment 1.

[0046] Example 5

[0047] The difference between this embodiment and the embodiment is that the amount of each component added is: 45 g of ammonia water in step (1), 800 g of anhydrous ethanol in step (1), and 9 g of nitric acid in step (2), and the rest is the same as in embodiment 1.

[0048] Example 6

[0049] The difference between this embodiment and the embodiment is that the addition amount of each component is: 5g of sodium perfluorooctane sulfonate, 15g of tetrabutyl titanate, and the others are the same as embodiment 1.

[0050] Example 7

[0051] The difference between this embodiment and the embodiment is that the addition amount of each component is: 7 g of sodium perfluorooctane sulfonate, 25 g of tetrabutyl titanate, and the rest is the same as embodiment 1.

[0052] The coating prepared in the embodiment of the present invention was tested for performance as follows:

[0053] Visible light transmittance: The visible light transmittance of the samples (coated-glass and original glass) was tested using an Agilent Cary 5000 UV-visible-near-infrared spectrophotometer. The size of the test sample was 7.5 cm × 2.5 cm, and a glass slide of the same size was selected as a control sample during the test. The transmittance of air was set as the baseline for the test. The test wavelength range was 300 nm to 1800 nm.

[0054] Emissivity in the infrared region: The emissivity of the coated photovoltaic panels in the long-wave infrared region (6-25 microns) was tested using the Thermo Fisher Nicolet iS50.

[0055] Contact angle: The contact angle of water droplets / oil droplets (if not otherwise specified, the oils used in the test here are all gasoline, i.e., a mixture of aliphatic hydrocarbons and cycloalkanes) on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For the measurement of the contact angle in a non-moving state, a water droplet / oil droplet (about 10 μL) was first added to the sample surface by a motor-controlled syringe. When the droplet is stable, a side image is taken with a camera, and the software is used for fitting calculation to obtain the static contact angle value of the water droplet / oil droplet on the coating surface.

[0056] Rolling / sliding angle: The sliding angle of water / oil droplets on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For sliding angle measurement, a motor-controlled rotatable test platform is used to tilt the sample, and the rotation angle of the platform is displayed in real time on a computer connected to the motor. At the beginning of the test, the initial inclination angle of the platform is maintained at 0°. After a water / oil droplet (~10μL) is added to the coating surface via a syringe, the motor is controlled to rotate the platform. The rotation stops at the moment the droplet begins to roll on the surface, and the rotation angle displayed on the computer is recorded as the rolling angle. Each sample is measured at three different positions to reduce data errors.

[0057] Anti-oil stain test: We first sprayed the coating on a 1 square centimeter glass substrate as a test sample, used fluorescent marker-labeled higher fatty acid glyceride as an oil stain simulant, and observed the samples before and after oil stain contamination and after light (30W power ultraviolet) degradation through an Olympus IX73 fluorescence microscope to characterize the anti-oil stain performance of the anti-oil stain photovoltaic panel self-cleaning coating. In order to further quantify the anti-oil stain performance of the coating, we weighed the mass of the sample before and after the addition of simulated oil stain pollutants and after light degradation. The specific quantitative indicators are as follows:

[0058]

[0059] Where Vdegradation is the average degradation rate constant, which is used to measure the average degradation rate of the coating for organic pollutants over a period of time; mbefore is the mass of the sample after the addition of simulated oil pollutants; mafter is the mass of the sample after the addition of simulated oil pollutants; mdrop is the mass of the sample after light degradation; t is the degradation time; and A is the sample area.

[0060]

[0061] In the formula, kdegradation is the degradation rate, which is used to measure the degree of degradation of organic pollutants by the coating; mbefore is the mass of the sample after the addition of simulated oil pollutants; mafter is the mass of the sample after the addition of simulated oil pollutants; and mdrop is the mass of the sample after light degradation.

[0062] In addition, we also conducted cyclic tests on the coating's light degradation process of oil stains to characterize the durability of the coating's anti-oil performance. We used a degradation rate of 95% as the dividing line. A degradation rate greater than 95% indicates effective performance, and a degradation rate less than 95% indicates performance failure. Therefore, we only record how many degradation-cleaning cycles the sample can maintain a degradation rate of 95% as a measurement indicator.

[0063] Comparative test of power generation efficiency: The current density-voltage curve is tested by the Taitai PROVA200A solar cell analyzer. The solar light source during the test is provided by the Yiguangke SOLARBEAM-06-3A sunlight simulator, simulating the irradiation intensity of AM 1.5 sunlight of about 100mW cm-2.

[0064] The coating performance tests prepared in each embodiment are shown in the following table:

[0065]

[0066]

[0067] like Figure 1 As shown, the anti-oil-fouling photovoltaic panel self-cleaning coating prepared by the present invention has nano-scale titanium dioxide particles embedded with an oil degradation agent, and the surface is grafted with sodium perfluorooctane sulfonate. The hydrophilic units (such as sodium ions) in the fluorinated sulfonate increase the orientation force component in the van der Waals force, thereby causing the coating to attract polar water molecules. The fluorine-containing groups minimize the dispersion force component in the van der Waals force, thereby causing the coating to repel oil molecules. The rutile TiO2 nanoparticles containing the bio-based oil degradation agent have, on the one hand, extremely high photocatalytic activity, allowing the coating to decompose organic pollutants on the surface under ultraviolet light; on the other hand, under the hydration of the hydrophilic layer, the oil degradation agent will be active, reduce the adhesion of surface oil, and can cooperate with photocatalysis to accelerate the degradation of organic pollutants.

[0068] pass Figure 2 The comparison curve of the transmittance of the coated photovoltaic panel glass and the untreated photovoltaic panel glass in the solar radiation spectrum region shows that the transmittance of the coated photovoltaic panel in the visible light region reaches about 92%, which is higher than that of the untreated glass. This may be because the nano-scale TiO2 layer acts as a transmittance-enhancing and anti-reflection layer, and the addition of fluorine-containing substances weakens the scattering effect of polar substances on light, thereby increasing the transmittance to a certain extent.

[0069] The contact angle of water droplets on the coated photovoltaic panel glass surface is about 0°, showing super hydrophilic properties; the contact angle of oil droplets on its surface is 86.8~94.9°, showing excellent oleophobic properties, and the sliding angle of oil droplets is 7.6~11°, which is the result of measurement in a dry state. In a high humidity environment with a hydration layer, the contact angle of oil droplets on the surface is about 72.1°, and the sliding angle is about 1.4°. When a hydration layer is present, the coating is more like a smooth oleophobic coating, and the hydration layer has an extremely high surface mobility, which can make surface-incompatible oil droplets quickly slide off the surface, which also gives the coating more outstanding anti-oil performance.

[0070] Figure 3 This is an image of the degradation performance of organic pollutants on the glass surface coated with the anti-greasy photovoltaic panel self-cleaning coating characterized by fluorescence microscopy (since it can only be expressed in black and white, the gray in the figure represents fluorescent green). In this test, we selected a glass substrate with an area of ​​1 square centimeter. After the surface was coated with the anti-greasy photovoltaic panel self-cleaning coating, organic pollutants marked with fluorescent markers were dripped on the surface. Under 30W ultraviolet irradiation, images were taken at the initial, 2 hours and 5 hours of irradiation to observe the degradation of surface organic pollutants. As can be seen from the figure, at the beginning of the experiment, the surface of the sample was a highly saturated fluorescent green, indicating that the surface was covered with fluorescently labeled organic pollutants; when the irradiation time reached 2 hours, the saturation of the fluorescent color weakened, indicating that the organic pollutants were reduced and the fluorescent markers were degraded with them; when the irradiation time reached 5 hours, there was almost no fluorescent color in the visible range, and it became completely black. Most of the organic pollutants and fluorescent markers were decomposed, indicating that the anti-greasy photovoltaic panel self-cleaning coating has excellent anti-greasy performance.

[0071] Figure 4 The anti-oil performance of the anti-oil photovoltaic panel self-cleaning coating was quantified by calculating the degradation rate of organic matter during the anti-oil test. After 5 hours of ultraviolet irradiation, the degradation rate of organic pollutants on the sample surface reached 97.5%. Figure 5As shown, in addition to the calculation of the degradation rate in a single degradation process, the average rate of the degradation process is also quantified, and the retention of the anti-oil performance after multiple degradation cycles is also evaluated, which can reflect the durability of the anti-oil performance of the anti-oil photovoltaic panel self-cleaning coating. Example 1 Preparation of the coating After 50 cycles of attachment-degradation-cleaning, the degradation rate of the anti-oil photovoltaic panel self-cleaning coating for surface pollutants can still be maintained at 0.07616 grams per hour per square centimeter, and the degradation rate is maintained at 95.2%. Even after 60 cycles, the degradation rate can still be maintained at 94.9%.

[0072] Figure 6 This is a test of the power generation efficiency of photovoltaic panels coated with anti-grease and self-cleaning coatings and untreated photovoltaic panels before and after being placed outdoors for one month. From the curves in the figure, we can see that before the test, the JV curves of the photovoltaic panels coated with the anti-grease and self-cleaning coatings and the untreated photovoltaic panels were roughly the same, and the short-circuit current and open-circuit voltage of the two photovoltaic panels were not much different, indicating that the power generation efficiency of the two was similar. After being placed outdoors for a month, since the untreated photovoltaic panels did not have self-cleaning properties, various organic and inorganic pollutants adhered to the surface, causing its power generation efficiency to drop sharply; while the photovoltaic panels coated with the anti-grease and self-cleaning coatings still had higher short-circuit current and open-circuit voltage, indicating that they can keep the surface clean for a long time without manual cleaning and maintain a higher power generation efficiency.

[0073] The present invention has been described in detail above in conjunction with specific embodiments. However, the present invention is not limited to the above description. Various changes made within the knowledge of those skilled in the art without departing from the concept of the present invention still fall within the protection scope of the present invention.

Claims

1. A self-cleaning coating for anti-grease photovoltaic panels, characterized in that: It comprises the following components: it comprises the following components in parts by weight: 17-20 parts of hollow nano titanium dioxide and 5-7 parts of sodium perfluorooctane sulfonate. The hollow nano titanium dioxide is hollow anatase nano titanium dioxide formed by coating the outer surface of silicon dioxide and then removing the silicon dioxide core. The hollow nano titanium dioxide contains an oil degradation agent.

2. The anti-grease and dirt self-cleaning coating for photovoltaic panels according to claim 1, characterized in that: The particle size of the nano titanium dioxide is 55-80nm.

3. The anti-grease and dirt self-cleaning coating for photovoltaic panels according to claim 1, characterized in that: The oil pollution degradation agent is a microbial-based oil pollution degradation agent.

4. A method for preparing a self-cleaning coating for anti-grease photovoltaic panels, characterized in that: It includes the following steps: 27-30 parts of hollow nano titanium dioxide containing an oil degradation agent are dispersed in a proper amount of volatile organic solvent, and then 5-7 parts of sodium perfluorooctane sulfonate are added dropwise to obtain an anti-oil stain coating.

5. The anti-grease and dirt self-cleaning coating for photovoltaic panels according to claim 4, characterized in that: The hollow nano titanium dioxide is a hollow anatase nano titanium dioxide formed by coating the outer surface of silicon dioxide and then removing the silicon dioxide core. The preparation method comprises the following steps: A1. Mix 25-34 parts of nano-silicon dioxide with an appropriate amount of ethanol, grind until there are no large-particle agglomerates visible to the naked eye, and then disperse them in an appropriate amount of water, add 3-9 parts of nitric acid, add 15-25 parts of tetrabutyl titanate, and then adjust the pH of the system to neutral, react for a period of time, and prepare a titanium dioxide sol-gel; the particle size of the nano-silicon dioxide is 55-80nm; A2. The titanium dioxide sol-gel is centrifuged, washed with ethanol to remove impurities, and then the ethanol is evaporated to remove the ethanol. The obtained nanopowder is heated to temperature T in a strong alkaline solution to be etched to remove nano-silicon dioxide, and then calcined at high temperature to obtain hollow nano-titanium dioxide.

6. The anti-grease and dirt self-cleaning coating for photovoltaic panels according to claim 4, characterized in that: The hollow nano titanium dioxide containing the oil degradation agent is prepared by the following steps: B1. Place hollow nano-titanium dioxide in a container, control the air pressure in the container to be lower than the atmospheric pressure, and inject an oil degradation agent into the container so that the oil degradation agent completely covers the nano-titanium dioxide particles; B2. Slowly release the system to normal air pressure to obtain hollow nano-titanium dioxide containing oil degradation agent.

7. The anti-grease and dirt self-cleaning coating for photovoltaic panels according to claim 5, characterized in that: The nano silicon dioxide is prepared by the following steps: C1. Mix 10-30 parts of water, 35-45 parts of industrial ammonia water, and 750-800 parts of ethanol, slowly add 30-40 parts of tetraethyl silicate, and react at 40-55° C. for a period of time to prepare SiO2 sol-gel; C2. After centrifuging the SiO2 sol-gel, the separated solid product is washed with ethanol, and then the ethanol is evaporated to obtain nano-silicon dioxide.

8. The anti-grease and dirt self-cleaning coating for photovoltaic panels according to claim 4, characterized in that: The volatile organic solvent is ethanol.

9. The method for preparing a self-cleaning coating for anti-grease photovoltaic panels according to claim 5, characterized in that: The temperature T is 82-88°C.

10. The method for preparing a self-cleaning coating for anti-grease photovoltaic panels according to claim 5, characterized in that: The calcination temperature in step A2 is 450°C.

Citation Information

Patent Citations

  • Photovoltaic module and preparation method of pollution-prevention coating layer of same

    CN108054227A

  • Titanium dioxide hollow nanospheres and preparation method thereof

    CN108675345A

  • Preparation method of hydrophilic-oleophobic coating in air

    CN117511259A

  • Preparation method for loading functional in organic micromolecules

    CN1795977A

Cited By

  • Self-cleaning waterproof coating and preparation method thereof

    CN120904739A